2018
DOI: 10.1111/cas.13887
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death ligand‐1 is associated with tumor infiltrating lymphocytes and poorer survival in urothelial cell carcinoma of the bladder

Abstract: Drugs blocking programmed death ligand‐1 (PD‐L1) have shown unprecedented activity in metastatic and unresectable bladder cancer. The purpose of the present study was to investigate the expression, clinical significance and association of PD‐L1 with tumor‐infiltrating lymphocytes (TIL) in resectable urothelial cell carcinoma of the bladder (UCB). In this retrospective study, 248 UCB patients who received radical cystectomy or transurethral resection were examined. Immunohistochemistry was used to evaluate PD‐L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 46 publications
7
74
2
Order By: Relevance
“…In contrast, we observed that UC patients with type II tumors (low tumor cell PD-L1 expression and low TILD) had a lower histological grade and lower pT stage than the other three groups, as well showing a favorable prognosis. Similarly, it has been reported in BUC that lower PD-L1 expression by tumor cells and a lower TILD are related to higher histological differentiation, noninvasiveness, and better survival [23]. Thus, our findings in UTUC may be in the same line than those in BUC in general.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, we observed that UC patients with type II tumors (low tumor cell PD-L1 expression and low TILD) had a lower histological grade and lower pT stage than the other three groups, as well showing a favorable prognosis. Similarly, it has been reported in BUC that lower PD-L1 expression by tumor cells and a lower TILD are related to higher histological differentiation, noninvasiveness, and better survival [23]. Thus, our findings in UTUC may be in the same line than those in BUC in general.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, slides of full-face hematoxylin and eosin-stained sections from primary tumors were retrieved for the evaluation of TILs by light microscopy [22,23]. Therein, we observed many mononuclear inflammatory cells in variable proportions, such as a small rounded cell and a large dark-stained nucleus with little eosinophilic cytoplasm.…”
Section: Assessment Of Tilsmentioning
confidence: 70%
See 1 more Smart Citation
“…Exosomal microRNAs (miRNAs), which are transferred by EVs, are promising and reliable tools for cancer diagnosis and clinical application [18]. PD-L1 overexpression has been examined as a prognostic factor in diverse cancers including lung cancer [19], gastric cancer [20], ovarian cancer [21], breast cancer [22], prostate cancer [23], bladder cancer [24], cervical cancer [25], cholangiocarcinoma [26], colorectal cancer [27], nasopharyngeal carcinoma [28], diffuse large B-cell lymphoma [29], pancreatic cancer [30], soft-tissue sarcoma [31], renal cell carcinoma [32], and head and neck squamous cell carcinoma [33]. In addition, in patients with melanoma, exosomal PD-L1 is an indicator of immune activation early after the initiation of treatment with immune checkpoint inhibitors (ICIs) and is associated with clinical response to ICIs [34].…”
Section: Introductionmentioning
confidence: 99%
“…Their studies indicated, however, that high heterogeneity of expression dependent on the type of cells expressing PD-L1 cells may lead to unreliable results [40]. Recent studies suggest that not only the level of PD-L1 expression in IECs may have a prognostic value but also their location and aggregation within the tumor may significantly affect survival [41,42]. Our findings indicate that there is a significant prognostic value of assessing the dispersed and aggregated patterns of distribution of PD-L1+ IECs within the tumor.…”
Section: Pd-l1 Expression In Pt1-pt4 Tumoursmentioning
confidence: 99%